2018
DOI: 10.1088/1741-2552/aadd1b
|View full text |Cite
|
Sign up to set email alerts
|

Delayed fatigue in finger flexion forces through transcutaneous nerve stimulation

Abstract: Our findings demonstrated that the stimulation of the proximal nerve bundles can elicit sustained force output and delayed decrease in the rate of force decline. This is potentially due to a spatially distributed activation of the muscle fibers, compared with the traditional motor point stimulation. Future development of our nerve stimulation approach may enable prolonged usage during rehabilitation or assistance for better functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The noninvasive stimulator introduced here was also used to provide a direct comparison of muscle stimulation and nerve stimulation for hand reanimation. Consistent with prior work, we show that both stimulation methods can reliably evoke muscle contractions 17 , 56 , 57 . Analysis of the individual trials indicated that muscle stimulation evoked larger forces at the beginning of an experimental block but decayed to less than the nerve stimulation forces by the end, resulting in higher fatigue rates for muscle stimulation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The noninvasive stimulator introduced here was also used to provide a direct comparison of muscle stimulation and nerve stimulation for hand reanimation. Consistent with prior work, we show that both stimulation methods can reliably evoke muscle contractions 17 , 56 , 57 . Analysis of the individual trials indicated that muscle stimulation evoked larger forces at the beginning of an experimental block but decayed to less than the nerve stimulation forces by the end, resulting in higher fatigue rates for muscle stimulation.…”
Section: Discussionsupporting
confidence: 90%
“…The adhesive electrodes were chosen primarily based on their widespread availability and ability to maintain electrical connection over long durations of time and when the participant moves. The adhesive electrodes are designed for primary use as measurement electrodes, and do not have optimal characteristics for stimulation; however, they are widely available and have acceptable electrical properties to serve as stimulation electrodes for research purposes 15 17 , 35 . Both forms of stimulation produced an isolated paresthesia-like, pins-and-needles, tingling, prickling, or electrical percept on the palm of the hand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments have demonstrated the capabilities of an alternative non-invasive transcutaneous electrical nerve stimulation method targeting the ulnar and median nerves proximal to the elbow to flexibly activate individual and multiple fingers (20, 21). In addition, this technique shows the ability to delay the force decline (22, 23). A stimulation electrode grid placed along the two nerves allows us to activate different muscles or muscle portions to elicit varied desired movements, but manually switching between different electrode pairs is time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, stimulation at the proximal segment of nerve bundles has been investigated (19, 20), in order to recruit a range of MUs, especially the more fatigue-resistant MUs. The nerve stimulation technique can result in less fatigable contractions (21) and more dexterous movements (22). In addition, the nerve bundle stimulation technique can activate afferent fibers with a low current amplitude and a high frequency (23), resulting in a more physiological recruitment order of MUs.…”
Section: Introductionmentioning
confidence: 99%